Location Choices of Chinese Multinationals in Europe: The Role of Overseas Communities - Bas Karreman; Martijn J. Burger; Frank G. van Oort (Tinbergen Institute, 2016)
Overseas Chinese communities are an important determinant in the location choice of greenfield investments made by mainland Chinese multinational enterprises across European regions. Conceptually embedded in a relational approach, this effect is shown through an empirical analysis of an exhaustive set of investment projects across NUTS-1 regions in 26 European countries for the period 2003-2010. When controlling for endogeneity bias and the embeddedness of existing Chinese economic activity, we find that the importance of overseas communities in the location choices of Chinese firms is based on increased access to strategic information. Our results confirm that the relationship between the size of an overseas Chinese community and the probability of Chinese investment is stronger for communities hosting newer generations of Chinese migrants; in addition, they partially corroborate that this relationship is stronger when the education level of the community's Chinese migrants is higher. Our findings are particularly robust in the context of knowledge-intensive sectors and high value-added functions.
Keywords: F20; L20; R30; 330; Overseas Chinese communities; China; Europe; greenfield FDI; relational view